Chapter 1 Trans-Imperial, Transnational and Decentralized The Traffic of African Slaves to Spanish America and Across the Isthmus of Panama, 1508-1651 - Garcia-Monton, Alejandro (Taylor & Francis, 2021)
history of the Americas